Prospective comparison of PI‐RADS version 2 and qualitative in‐house categorization system in detection of prostate cancer. Issue 5 (31st March 2018) - Gaur, Sonia; Harmon, Stephanie; Mehralivand, Sherif; Bednarova, Sandra; Calio, Brian P.; Sugano, Dordaneh; Sidana, Abhinav; Merino, Maria J.; Pinto, Peter A.; Wood, Bradford J.; Shih, Joanna H.; Choyke, Peter L.; et al.
Abstract : Background: Prostate Imaging‐Reporting and Data System v. 2 (PI‐RADSv2) provides standardized nomenclature for interpretation of prostate multiparametric MRI (mpMRI). Inclusion of additional features for categorization may provide benefit to stratification of disease. Purpose: To prospectively compare PI‐RADSv2 to a qualitative in‐house system for detecting prostate cancer on mpMRI. Study Type: Prospective. Population: In all, 338 patients who underwent mpMRI May 2015–May 2016, with subsequent MRI/transrectal ultrasound fusion‐guided biopsy. Field Strength: 3T mpMRI (T2 W, diffusion‐weighted [DW], apparent diffusion coefficient [ADC] map, b‐ 2000 DWI acquisition, and dynamic contrast‐enhanced [DCE] MRI). Assessment: One genitourinary radiologist prospectively read mpMRIs using both in‐house and PI‐RADSv2 5‐category systems. Statistical Test: In lesion‐based analysis, overall and clinically significant (CS) tumor detection rates (TDR) were calculated for all PI‐RADSv2 and in‐house categories. The ability of each scoring system to detect cancer was assessed by area under receiver operator characteristic curve (AUC). Within each PI‐RADSv2 category, lesions were further stratified by their in‐house categories to determine if TDRs can be increased by combining features of both systems. Results: In 338 patients (median prostate‐specific antigen [PSA] 6.5 [0.6–113.6] ng/mL; age 64 [44–84] years), 733 lesions were identified (47% tumor‐positive). Predictive abilities of both systems were comparable for all (AUC 76–78%) and CS cancers (AUCs 79%). The in‐house system had higher overall and CS TDRs than PI‐RADSv2 for categories 3 and 4 ( P < 0.01 for both), with the greatest difference between the scoring systems seen in lesions scored category 4 (CS TDRs: in‐house 65%, PI‐RADSv2 22.1%). For lesions categorized as PI‐RADSv2 = 4, characterization of suspicious/indeterminate extraprostatic extension (EPE) and equivocal findings across all mpMRI sequences contributed to significantly different TDRs for both systems (TDR range 19–75%, P < 0.05). Data Conclusion: PI‐RADSv2 behaves similarly to an existing validated system that relies on the number of sequences on which a lesion is seen. This prospective evaluation suggests that sequence positivity and suspicion of EPE can enhance PI‐RADSv2 category 4 cancer detection. Level of Evidence: 1 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2018;47:1326–1335.